Ischemic stroke in COVID‐19 patients: Mechanisms, treatment, and outcomes in a consecutive Swiss Stroke Registry analysis. (9th December 2021) - Strambo, Davide; De Marchis, Gian Marco; Bonati, Leo H.; Arnold, Marcel; Carrera, Emmanuel; Galletta, Santi; Nedeltchev, Krassen; Kahles, Timo; Cereda, Carlo W.; Bianco, Giovanni; Kägi, Georg; Luft, Andreas R.; et al.
Abstract: Background: Most case series of patients with ischemic stroke (IS) and COVID‐19 are limited to selected centers or lack 3‐month outcomes. The aim of this study was to describe the frequency, clinical and radiological features, and 3‐month outcomes of patients with IS and COVID‐19 in a nationwide stroke registry. Methods: From the Swiss Stroke Registry (SSR), we included all consecutive IS patients ≥18 years admitted to Swiss Stroke Centers or Stroke Units during the first wave of COVID‐19 (25 February to 8 June 2020). We compared baseline features, etiology, and 3‐month outcome of SARS‐CoV‐2 polymerase chain reaction‐positive (PCR+) IS patients to SARS‐CoV‐2 PCR− and/or asymptomatic non‐tested IS patients. Results: Of the 2341 IS patients registered in the SSR during the study period, 36 (1.5%) had confirmed COVID‐19 infection, of which 33 were within 1 month before or after stroke onset. In multivariate analysis, COVID+ patients had more lesions in multiple vascular territories (OR 2.35, 95% CI 1.08–5.14, p  = 0.032) and fewer cryptogenic strokes (OR 0.37, 95% CI 0.14–0.99, p  = 0.049). COVID‐19 was judged the likely principal cause of stroke in 8 patients (24%), a contributing/triggering factor in 12 (36%), and likely not contributing to stroke in 13 patients (40%). There was a strong trend towards worse functional outcome in COVID+ patients after propensity score (PS) adjustment for age, stroke severity, and revascularization treatments (PS‐adjusted common OR for shift towards higher modified Rankin Scale (mRS) = 1.85, 95% CI 0.96–3.58, p  = 0.07). Conclusions: In this nationwide analysis of consecutive ischemic strokes, concomitant COVID‐19 was relatively rare. COVID+ patients more often had multi‐territory stroke and less often cryptogenic stroke, and their 3‐month functional outcome tended to be worse. Abstract : In a nationwide Swiss analysis of consecutive ischemic strokes, concomitant COVID‐19 was relatively rare. COVID+ patients more often had multi‐territory stroke and less often cryptogenic stroke, and their 3‐month functional outcome tended to be worse.